PERENDAMAN BENIH SAGA (Adenanthera pavonina L.) DENGAN BERBAGAI KONSENTRASI AIR KELAPA UNTUK MENINGKATKAN KUALITAS KECAMBAH - Antoni Tampubolon; M. Mardiansyah '; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aimed to determine the effect of soaking Adenanthera pavonina in various of coconut water concentration to improve the quality of seed germinated and know the best concentration Adenanthera pavoninasoaking in coconut water to maintain the quality of seed germinated. The research method used in completely randomized design (CRD) with 4 treatments, 1 control and 3 replications. The treatment consisted  of: K0= saga seeds without soaking coconut water; K1=soakingsaga seeds in 25% coconut water; K2= soaking saga seeds in 50% coconut water; K3= soaking sagaseeds in 75% coconut water; K4= soaking sagaseeds in 100% coconut water. Research has shown that soaking the Adenanthera pavonina seedin 50% coconut water has significant effect tothe high increase of seed germination(10,3cm) and soaking the Adenanthera pavonina seed in coconut water has no significant effect on power of germinated, speed of seed germinated, speed ofseed germination at 80% and percentage of seeds germinated Keywords :Adenanthera pavonina, coconut water, seed quality.